Keberhasilan Usaha Industri Mikro Kecil Menengah Makanan Ringan di Priangan Barat Pendekatan Lingkungan Usaha, Manajemen Usaha, Kreativitas, dan Inovasi - Dwi Gemina; Sri Harini (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
The development of the micro, small, medium industry has rapid growth and development because it is able to survive amid the conditions of the economic crisis. The objectives of this study were: 1) to analyze the influence of business environment, business management and creativity and innovation on business success simultaneously and partially in West Priangan; 2) Factors driving and inhibiting business success in West Priangan. Survey research methods and forms of descriptive and verification research. The research object of snack MSMI in West Priangan was 150 respondents. Sampling using random sampling techniques is based on areas that have the potential for industrial development (industrial centers) consisting of three regions, namely Bogor, Sukabumi and Cianjur. Then the questionnaire was tested with validity and reliability tests. The results of the test data were declared valid and reliable and carried out a classic assumption test for use in the regression test. The results showed that simultaneously the business environment, business management and creativity and innovation had a positive and significant effect on the success of business in West Priangan. Partially the business environment, business management and creativity have a positive and significant effect on business success. Innovation does not have a positive and significant effect on business success. Meanwhile, the driving factors for business success are the business environment, business management and creativity, and innovation is an inhibiting factor for business success.